Kontribusi Kualitas Asset Produktif (KAP) dan Non Performing Loan (NPL) Bank Perkreditan Rakyat Konvensional (BPRK) Era Covid-19 terhadap Capital Adequacy Ratio (CAR) melalui Profitabilitas (ROA). (Studi Empiris pada BPR Konvensional di wilayah Kantor - Mulyaningsih Mulyaningsih; Taofik Hidajat (Magister Manajemen STIE Bank BPD Jateng, 2022)
This study aims to determine the contribution of Productive Asset Quality (KAP) and Non Performing Loans (NPL) to the Capital Adequacy Ratio (CAR) with profitability (ROA) as an intervening variable at Conventional Rural Banks (BPRK) in the area of ​​the Kantor Otoritas Jasa Keuangan (KOJK). From the second quarter of 2020 to the third quarter of 2021, the research sample consisted of 30 BPRK with a total of 180 research data. Data were collected using the cluster sampling method. Path analysis technique was used to analyze the data. The results of the analysis show that Productive Asset Quality (KAP) has a positive and insignificant effect on the Capital Adequacy Ratio (CAR). Non-Performing Loan (NPL) has an insignificant negative effect on the Capital Adequacy Ratio (CAR). Productive Asset Quality (KAP) has a significant positive effect on profitability (ROA). Non-Performing Loan (NPL) has a significant negative effect on profitability (ROA). Profitability (ROA) has a significant positive effect on the Capital Adequacy Ratio (CAR). And profitability (ROA) does not significantly mediate the effect of Productive Asset Quality (KAP) and Non-Performing Loans (NPL) on the Capital Adequacy Ratio (CAR).